Bioactivities of Stixis suaveolens (Roxb.) Fruit Extract: An Evaluation in Mice Model (Bangladesh Pharmaceutical Journal, 2020)
The fruits of Stixis suaveolens (Roxb.) have been a popular folk medicine among traditional practitioners. However, there are questions about its traditional uses due to lack of scientific evidence. This study was aimed to evaluate the effects of crude methanol extract of fruits of S. suaveolens in mice model. The central and peripheral analgesic activity were evaluated using the ‘tail flick’ and ‘writhing’ assay respectively. The anti-hyperglycemic potential was assessed by the ability of the crude extract in reducing blood glucose level in mice after oral administration of glucose. Oral administration (400 mg/kg bw) of the extract showed significant (p